Phylogenetic evidence of a rapid radiation of pleurocarpous mosses (Bryophyta) - Shaw, A. J. (2014)
Pleurocarpous mosses, characterized by lateral female gametangia and highly branched, interwoven stems, comprise three orders and some 5000 species, or almost half of all moss diversity. Recent phylogenetic analyses resolve the Ptychomniales as sister to the Hypnales plus Hookeriales. Species richness is highly asymmetric with approximately 100 Ptychomniales, 750 Hookeriales, and 4400 Hypnales. Chloroplast DNA (cpDNA) sequences were obtained to compare partitioning of molecular diversity among the orders with estimates of species richness, and to test the hypothesis that either the Hookeriales or Hypnales underwent a period (or periods) of exceptionally rapid diversification. Levels of biodiversity were quantified using explicitly historical ‘‘phylogenetic diversity’’ and nonhistorical estimates of standing sequence diversity. Diversification rates were visualized using lineage-through-time (LTT) plots, and statistical tests of alternative diversification models were performed using the methods of Paradis (1997). The effects of incomplete sampling on the shape of LTT plots and performance of statistical tests were investigated using simulated phylogenies with incomplete sampling. Despite a much larger number of accepted species, the Hypnales contain lower levels of (cpDNA) biodiversity than their sister group, the Hookeriales, based on all molecular measures. Simulations confirm previous results that incomplete sampling yields diversification patterns that appear to reflect a decreasing rate through time, even when the true phylogenies were simulated with constant rates. Comparisons between simulated results and empirical data indicate that a constant rate of diversification cannot be rejected for the Hookeriales. The Hypnales, however, appear to have undergone a period of exceptionally rapid diversification for the earliest 20% of their history.